2008
DOI: 10.1177/0269215507083795
|View full text |Cite
|
Sign up to set email alerts
|

Serial casting versus positioning for the treatment of elbow contractures in adults with traumatic brain injury: a randomized controlled trial

Abstract: Serial casting induces transient increases in range of motion. These effects are not maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…Elbow extension was measured using the method described by Moseley et al (intraclass correlation coefficient ¼ 0.98, 95% CI 0.93-1). 10 Wrist extension was measured using the method described by Harvey et al (intraclass correlation coefficient ¼ 0.85). 11 Ankle dorsiflexion was measured at 12 Nm of torque with a spring balance and cuff secured over the foot using a procedure similar to that described by Moseley and Adams.…”
Section: Measures Of Contracturementioning
confidence: 99%
“…Elbow extension was measured using the method described by Moseley et al (intraclass correlation coefficient ¼ 0.98, 95% CI 0.93-1). 10 Wrist extension was measured using the method described by Harvey et al (intraclass correlation coefficient ¼ 0.85). 11 Ankle dorsiflexion was measured at 12 Nm of torque with a spring balance and cuff secured over the foot using a procedure similar to that described by Moseley and Adams.…”
Section: Measures Of Contracturementioning
confidence: 99%
“…However, passive joint mobility can be improved by serial casting. A follow-up treatment with splints is often indispensable, which is impressively evidenced in a paper by Moseley et al, [15]: serial casting results showed an average improvement of elbow mobility by 22 degrees. However, this range of motion already decreased by 11 degrees on the subsequent day and completely disappeared after 4 weeks.…”
Section: Resultsmentioning
confidence: 98%
“…6,8,[12][13][14][15][16][17][18][19][20][21] These findings were confirmed by a recent Cochrane review that provided high-quality evidence that passive stretch produces negligible short-term (mean between-group difference 1 , 95% CI, 0-3) or long-term (mean between-group difference 0 , 95% CI, À2 to 2) changes in joint range of motion (ROM) when administered to people with a variety of neurological conditions. The typical dose of passive stretch applied in the reported trials was 30 minutes to 12 hours per day over 4-12 weeks (median duration 30 days); 22 this dosage of passive stretch may be insufficient.…”
mentioning
confidence: 76%